2019
DOI: 10.1002/jcb.28522
|View full text |Cite
|
Sign up to set email alerts
|

TET1 suppresses colon cancer proliferation by impairing β‐catenin signal pathway

Abstract: The function of ten-eleven translocation methylcytosine dioxygenase 1 (TET1) in cancer is background dependent and may be involved in the initial step of active DNA demethylation, while there is little research to decipher the role of TET1 in DNA methylation-sensitive colon cancer. Downregulated TET1 expression assayed by quantitative real-time PCR (qRT-PCR) was observed in both colon cancer samples and cancer cell lines of HT29, HCT116, and SW48. Such downregulation could promote colon cancer cells proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
(51 reference statements)
2
13
0
1
Order By: Relevance
“…21 More recently, a study also indicated that TET1 overexpression was considerably associated with cell proliferation in colon cancer cells. 22 Correspondingly, our results also indicated that overexpression of TET1 inhibited cell growth of GC cells. Besides, overexpression of TET1 also inhibited cell migration and invasive capabilities of GC cells, consistent with previous results in hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 71%
“…21 More recently, a study also indicated that TET1 overexpression was considerably associated with cell proliferation in colon cancer cells. 22 Correspondingly, our results also indicated that overexpression of TET1 inhibited cell growth of GC cells. Besides, overexpression of TET1 also inhibited cell migration and invasive capabilities of GC cells, consistent with previous results in hepatocellular carcinoma.…”
Section: Discussionsupporting
confidence: 71%
“…TET3 regulates the proliferation of HepG2 cells [26]. Compared with hepatocellular carcinoma, our results indicated that increased TET1 expression induced apoptosis and inhibited the growth of U2OS cells, consistent with previous data obtained from colon cancer cells [27]. TET1 expression was recently reported to be associated with apoptosis in bladder cancer cells [28].…”
Section: Discussionsupporting
confidence: 90%
“…Accumulating evidence has discovered that TET1 played important roles in the occurrence and development of neoplastic diseases [23,24]. It has reported that overexpression of TET1 could signi cantly inhibit cell growth, migration and invasion of colon cancer and cervical cancer [23,25,26]. In addition, the recent study also found that TET1 involved in p53 mediated lung cancer cellular aging as an oncogene [27].…”
Section: Discussionmentioning
confidence: 98%